PYCR1 interference inhibits cell growth and survival via c-Jun N-terminal kinase/insulin receptor substrate 1 (JNK/IRS1) pathway in hepatocellular cancer - Juhua Zhuang; Yanan Song; Ying Ye; Saifei He; Xing Ma; Miao Zhang; Jing Ni; Jiening Wang; Wei Xia (Journal of Translational Medicine, 2019)
Abstract Background Liver cancer is the second leading causes of cancer-related death globally. Pyrroline-5-carboxylate reductase 1 (PYCR1) plays a critical role in metabolic profiles of tumors. Therefore, it is necessary to explore the mechanisms of PYCR1 on cell growth and survival in hepatocellular carcinoma (HCC). Methods Protein and mRNA expression levels of PYCR1 in 140 pairs of tumor and adjacent normal liver tissues of HCC patients were analyzed by immunohistochemistry and quantitative real-time polymerase chain reaction (qRT-PCR). Expressions of PYCR1 were inhibited in BEL-7404 cells and SMMC-7721 cells using gene interference technology. The cell proliferation was detected by Celigo and MTT assay. The colony formation assay was also performed. The cell apoptosis was measured by flow cytometric assay. The effect of PYCR1 interference on tumor growth was observed by xenograft nude mice assay in vivo. The downstream pathway of PYCR1 interference was searched by microarray and bioinformatics analysis, and validated by qRT-PCR and western blot. Results PYCR1 levels were significantly up-regulated in HCC tumor tissues than adjacent normal liver tissues in both protein and mRNA levels (P < 0.01). In vitro, the cell proliferation was significantly slower in shPYCR1 group than shCtrl group in BEL-7404 and SMMC-7721 cells (P < 0.001). The colony number was significantly smaller after PYCR1 interference (P < 0.01). The percentage of apoptosis cells significantly increased in shPYCR1 group (P < 0.01). In vivo, PYCR1 interference could obviously suppress tumor growth in xenograft nude mice. The volume and weight of tumors were significantly smaller via PYCR1 interference. The c-Jun N-terminal kinase (JNK) signaling pathway significantly altered, and insulin receptor substrate 1 (IRS1) were significantly down-regulated by PYCR1 interference in both mRNA and protein levels (P < 0.001). Conclusion PYCR1 interference could inhibit cell proliferation and promote cell apoptosis in HCC through regluting JNK/IRS1 pathway. Our study will provide a drug target for HCC therapy and a potential biomarker for its diagnosis or prognosis.